Ambient noise tomography of the Aegean region of Türkiye from Rayleigh wave group velocity - Mulumulu, Emre; Polat, Orhan; Chávez-García, Francisco J. (Frontiers in Earth Science, 2023)
We have studied Rayleigh wave group velocities beneath the Aegean region of Turkiye using ambient noise tomography. Noise data were gathered from 43 broadband seismic stations belonging to three permanent broad-band arrays. The cross-correlation method was used to estimate empirical Green's functions. Group velocities of the fundamental mode Rayleigh waves were determined using multiple filter technique. We measured dispersion for each station pair in a period range of 2-12 s and computed maps of group velocity distribution using fast marching surface tomography method. The group velocity maps correlate well with the geological and tectonic features of the region, displaying low velocities for the Quaternary alluvial basins, moderate velocities for Cretaceous rocks, and high velocities for the regions where gneiss and granitoid rocks outcrop. Low velocity anomalies may be associated with the grabens and horsts formed by faulting and to deep mantle flow. We detect potential offshore geothermal zones in Izmir and Candarli Bay. The information from broad-band networks improves the resolution of crustal surface wave velocity structures, particularly for shallow depths. This improvement will support the assessment of seismic hazard, as the shallow layers of the crust contribute significantly to seismic activity. Alluvial sediments in grabens were deposited during the early Miocene (Jolivet et al., 2013) when the north-south extension created east-west aligned grabens and horsts structures with an elevation up to 1500 m (Yilmaz et al., 2000). The shaded relief topography shown in Figure 1 correlates well with the tectonic and geomorphologic structures in the study area.During the Oligocene-Middle Miocene, there was widespread magmatic activity in Western Anatolia, which waned at the end of Middle Miocene. This intrusive volcanism produced high mountain ranges aligned northeast-southwest. A new set of northeast-southwest trending oblique faults were formed under the transtensional regime. This produced other grabens (e.g. Bakircay-BG placed between Gordes and Selendi cities) and horst systems. During Miocene-Pliocene, the horst-graben morphology was considerably reduced as a result of severe erosion (Yang et al., 2021). Consequently, low-relief narrow plateau and horst surfaces were established. The Early to Middle Miocene volcanics, marls and pyroclastic rocks widely outcrop around those horsts.